A case of type B insulin resistance syndrome treated with low-dose glucocorticoids. (12th November 2019) - Kotani, Masato; Tamura, Naohisa; Inoue, Tatsuhide; Tanaka, Issei
Abstract : Summary: Type B insulin resistance syndrome is characterized by the presence of autoantibodies to the insulin receptor. We present a 57-year-old male admitted to a hospital due to body weight loss of 16 kg and hyperglycemia of 13.6 mmol/L. He was diagnosed with type B insulin resistance syndrome because the anti-insulin receptor antibodies were positive. We informed him that some hyperglycemic cases of this syndrome had been reported to be spontaneously remitted in 5 years, and he did not agree to be treated with high-dose glucocorticoids and/or immunosuppressive agents due to his concern for their adverse effects such as hyperglycemia and immunosuppression. He chose to be treated with insulin and voglibose, but fair glucose control could not be obtained. Six years later, he agreed to be treated with low-dose glucocorticoids practicable in outpatient settings. One milligram per day of betamethasone was tried orally and reduced gradually according to the values of glycated hemoglobin. After 30 months of glucocorticoid treatment, the anti-insulin receptor antibodies became undetectable and his fasting plasma glucose and glycated hemoglobin were normalized. This case suggests that low-dose glucocorticoids could be a choice to treat type B insulin resistance syndrome in outpatient settings. Learning points: Type B insulin resistance syndrome is an acquired autoimmune disease for insulin receptors. This case suggested the possibility of long-lasting, low-dose glucocorticoid therapy for the syndrome as an alternative for high-dose glucocorticoids or immunosuppressive agents. Since the prevalence of autoimmune nephritis is high in the syndrome, a delay of immunosuppressive therapy initiation might result in an exacerbation of nephropathy.